Aneurysmal mandibular bone cyst - Denia Morales Navarro; Carlos Guillermo Camacho Olguín (Editorial Ciencias Médicas, 2016)
Introduction: aneurysmal bone cyst is defined as an expansive osteolytic lesion consisting of blood-filled spaces and divided by partitions of connective tissue and osteoid tissue containing giant cells channels. Objective: to present a rare case of aneurysmal bone cyst in the region of the mandibular body. Case report: a 39 years old female patient who attended outpatient service of Maxillofacial Surgery, University Hospital "General Calixto García" by increased volume in right mandible and pain of 1 month of evolution. Radiographically one unilocular radiolucent area of sharp edges, performing curettage of the cavity and histopathology of the lesion which reported the presence of an aneurysmal bone cyst was detected. Conclusion: aneurysmal bone cyst is most commonly detected in the long bones and in the region of the mandibular angle in the facial skeleton, so that the presentation of this in the mandibular body, in the case presented, is an attraction for presentation.